2015
DOI: 10.1016/j.jpsychires.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid amyloid-β levels in late-life depression: A systematic review and meta-analysis

Abstract: This study aimed to evaluate differences in plasma and cerebrospinal fluid (CSF) levels of Aβ peptides in older adults with late-life depression compared to non-depressed older controls. We conducted a systematic review and meta-analysis of the literature using PubMed, Web of science and Scopus databases with no search limits for publication dates or languages. Two independent reviewers extracted data and assessed quality. Six hundred references were retrieved, and we included 12 studies in the meta-analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 60 publications
2
47
0
2
Order By: Relevance
“…Indeed, a previous DTI–tract based spatial statistics (TBSS) analysis on the same sample suggested subtle deficits of integrity in white matter fibers within frontal, temporal, and midbrain regions (Colloby et al., 2011). In addition to microstructural alterations in white matter, the pathophysiological background of LLD is complicated by a host of factors, including vascular, neurotransmitter disruptions, and amyloidosis reminiscent of Alzheimer's disease pathology (Nascimento et al., 2015). Collectively, the broad range of changes in LLD has given rise to the notion that LLD could be characterized as a systems-level disorder, one that is particularly suited to be investigated by a multivariate network approach that considers the orchestrated interactions between distinct neuroanatomical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous DTI–tract based spatial statistics (TBSS) analysis on the same sample suggested subtle deficits of integrity in white matter fibers within frontal, temporal, and midbrain regions (Colloby et al., 2011). In addition to microstructural alterations in white matter, the pathophysiological background of LLD is complicated by a host of factors, including vascular, neurotransmitter disruptions, and amyloidosis reminiscent of Alzheimer's disease pathology (Nascimento et al., 2015). Collectively, the broad range of changes in LLD has given rise to the notion that LLD could be characterized as a systems-level disorder, one that is particularly suited to be investigated by a multivariate network approach that considers the orchestrated interactions between distinct neuroanatomical regions.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in CSF Aβ42 levels has been used to diagnose AD. 11 Increased plasma Aβ42 levels and a decreased Aβ40-to-42 ratio have been reported in older patients with depression. 7 However, a recent study that measured plasma Aβ levels by immunoprecipitation coupled with mass spectrometry showed that plasma Aβ levels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the Aβ40/Aβ42 ratio) correlated with CSF Aβ42 levels and amyloid deposition through Aβ positron emission tomography imaging, suggesting that plasma Aβ levels might predict the burden of Aβ in the brain. 11 These studies exploring peripheral Aβ levels in patients with depression involved only older adults. older individuals have shown that a higher baseline plasma Aβ40-to-Aβ42 ratio might increase the risk of developing AD.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we analysed different systems, such as the endocannabinoid system [19,20], sphingolipids [21] and the hormone Klotho [22,23], all, which have been just recently linked to depression. Additionally, we analysed markers of neurodegeneration, which are mainly associated to Alzheimer's disease (AD) but have also shown to be associated with depression [24][25][26].…”
Section: Introductionmentioning
confidence: 99%